Analisis Aspek Sosial dalam Novel “Laskar Pelangi” Karya Andrea Hirata - Nur Aisyah; Fatharani Ghaida Zahirah Jufri (Studi Administrasi Publik dan ilmu Komunikasi, 2024)
This study aims to analyze the social aspects in the novel Laskar Pelangi by Andrea Hirata. This novel depicts the social reality of the Belitong Malay community which faces various challenges, especially in the fields of education, economy, and culture. Through a literary sociology approach, this analysis reveals how social, economic, and cultural backgrounds shape the characters and conflicts in the story. The results of the study show that the novel Laskar Pelangi represents the struggle of the lower class in accessing education, the social inequality that occurs due to the exploitation of natural resources by mining companies, as well as the spirit of friendship and solidarity that is a strength in facing difficulties. This novel not only inspires readers with its moral messages but also reflects the complex and dynamic social conditions of Indonesian society.